2017
DOI: 10.1002/slct.201701493
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Nano-SiO2 Particles with Polycarboxylate Ether-Based Superplasticizer under Microwave Irradiation

Abstract: The mechanical properties and durability of cement‐based materials reinforced by nano‐SiO2 (NS) particles are strongly dependent on the dispersion characteristics of the latter. This study presents an innovative eco‐friendly method, which improves the distribution of NS particles through their surface modification using polycarboxylate ether‐based (PCE) superplasticizer containing silane coupling agent under microwave irradiation. The above method ensures the formation of a core‐shell‐shell structure, wherein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…After 11 h, peak intensity of the hydration product increased, indicating that more ettringite formed. While, because Al(OH) 3 and Fe(OH) 3 gels were poorly crystallized or amorphous, they were not detected in the pastes. It was observed that the incorporation of PC significantly lowered the characteristic peak of ettringite compared with the blank FAC sample at the ages of 5 h and 11 h, which is consistent with the setting time and hydration heat tests.…”
Section: Xrd Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…After 11 h, peak intensity of the hydration product increased, indicating that more ettringite formed. While, because Al(OH) 3 and Fe(OH) 3 gels were poorly crystallized or amorphous, they were not detected in the pastes. It was observed that the incorporation of PC significantly lowered the characteristic peak of ettringite compared with the blank FAC sample at the ages of 5 h and 11 h, which is consistent with the setting time and hydration heat tests.…”
Section: Xrd Analysismentioning
confidence: 94%
“…As the most important building material, Portland cement has been widely used in engineering construction worldwide. However, in the manufacturing process of Portland cement clinker, the decarbonation and calcination process produce approximately 5-8% of global anthropogenic CO 2 emissions [1][2][3][4][5]. One of the ways to reduce CO 2 emission from Portland cement production is to replace Portland cement with Calcium sulfoaluminate.…”
Section: Introductionmentioning
confidence: 99%
“…As observed, the broad peak at 3490 cm À 1 was identified as the characteristic peak of À OH in PCE. The peak at 2880 cm À 1 corresponded to the À CÀ H group, and the peak at 1160 cm À 1 was attributed to the vibrational peak of CÀ OÀ C. [32,33] The characteristic peak of C=C in chain transfer agent, which was supposed to appear at 1630 cm À 1 , was not observed. Overall, the three sulfhydryl chain transfer agents had the chain transfer effect, realizing the successful polymerization of PCE.…”
Section: Characterization Of the Pcesmentioning
confidence: 98%
“…To answer these challenges, some researchers started to promote changes in the NS surface (or NS functionalization) in order to create adaptations according to the need (Azevedo & Gleize, 2018;Collodetti et al, 2014;Gu et al, 2016Gu et al, , 2018Huang & Wang, 2017;Monasterio et al, 2015;Perez et al, 2015). The functionalization of nanosilica is a chemical process that consists of adding new chemical functions to the NS surface.…”
Section: Introductionmentioning
confidence: 99%